Development of the model of forced-exhaust ventilation for passenger carriages - Бушер, Виктор Владимирович; Ярмолович, Виктория Ярославовна (Eastern-European Journal of Enterprise Technologies, 2016)
The behavior analysis of the model of forced-exhaust ventilation for the passenger compartment carriage, based on the principle of similarity with electric circuits is performed. For quality indicators of the control object, the parameters of resistance and relative inductances determining the aerodynamic inertia of ducts and compartments are included in the model. The computations produced the charts of transients of air flows in individual compartments and the total flow. Their analysis suggests that despite the model formation only of the objects described by the first-order differential equations, the equivalent models of the carriage and individual compartments may be characterized by fractional order of differential equations. This allows us to offer a method of identifying the dynamic parameters of individual sections of the air duct and the compartment by fractional aperiodic links. Such links are a special case of the hyper-neuron. Their parameters are well defined using genetic algorithms. This reduced the order of equivalent transfer functions to 0.9...1.8 with a relative mean square error between the results of the ventilation system model transients and the solutions of fractional differential equations of no more than 0.14...1.23%.The results indicate the feasibility of constructing a control system for the ventilation unit using the theory of fractional integral-differential controllers.